The Role of Physical and Sexual Assaults on the Ability to Complete Work Responsibilities. Issue 17 (September 2021) - Posick, Chad; Jackson, Dylan B.; Grubb, Jonathan A.
Sexual and physical assaults have many serious and persistent negative impacts on individual health. There is now a considerable literature base identifying and discussing these health outcomes. Less is known about the mediating mechanisms that link these types of assault with later outcomes. This study examines the role of sexual and physical assaults in self-perceptions of individual health on missing or cutting back on work responsibilities. In particular, perceptions of both mental and physical health are investigated to further refine understanding of the different impacts of assault on survivor health and behavior. Using a sample of 3, 791 adults aged 30 to 84 from the Midlife in the United States (MIDUS) study, results of the analyses indicate that sexual and physical assaults do not have a direct effect on missing/cutting back on work responsibilities but do have an indirect effect through perceptions of health. The results can inform academic research, as important impacts of assault may be masked if mediating mechanisms are not investigated. In terms of policy, adults who have difficulty carrying out work responsibilities should be assessed for their overall health and survivors of violence should be offered health-related services following a victimization experience.